2022
DOI: 10.2106/jbjs.21.01168
|View full text |Cite
|
Sign up to set email alerts
|

Modular Fluted Tapered Stems for Periprosthetic Femoral Fractures

Abstract: Background:Modular fluted tapered (MFT) stems have advanced treatment of Vancouver B2 and B3 periprosthetic femoral fractures, but series to date have been limited with respect to cohort size and follow-up duration. The purpose of this study was to determine implant survivorship, radiographic results, complications, and clinical outcomes of Vancouver B2 and B3 periprosthetic femoral fractures treated with MFT stems in a large series of patients.Methods:We identified 171 Vancouver B2 (109) and B3 (62) periprost… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
8
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 11 publications
(9 citation statements)
references
References 33 publications
1
8
0
Order By: Relevance
“…Contemporary series have demonstrated that the use of a modular fluted tapered stem leads to improved implant survivorship and clinical outcomes with lower complication rates for Vancouver B2 and B 3 periprosthetic femoral fractures 1,10-12,14-19 .…”
Section: Expected Outcomesmentioning
confidence: 99%
See 2 more Smart Citations
“…Contemporary series have demonstrated that the use of a modular fluted tapered stem leads to improved implant survivorship and clinical outcomes with lower complication rates for Vancouver B2 and B 3 periprosthetic femoral fractures 1,10-12,14-19 .…”
Section: Expected Outcomesmentioning
confidence: 99%
“…As a result of these unique advantages, these stems were introduced several years ago for the treatment of Vancouver B 2 or B 3 periprosthetic femoral fractures. Expected Outcomes: Contemporary series have demonstrated that the use of a modular fluted tapered stem leads to improved implant survivorship and clinical outcomes with lower complication rates for Vancouver B2 and B 3 periprosthetic femoral fractures 1,[10][11][12][14][15][16][17][18][19] . Important Tips:…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…These have shown challenges in management due to difficulties in treating the fracture in tandem with managing the loose implant, requiring revision total hip arthroplasty (rTHA) surgery, as well as fracture fixation. [1][2][3][4] UCS B2 and B3 fractures have been traditionally managed with the use of modular long porous-coated tapered cementless stems with optional use of proximal bone allograft and cerclage cables. 3,[5][6][7][8] The construct popularity has been attributed to multiple factors, such as control in the adjustment of leg length, neck anteversion, and offset following implantation of the distal fixation portion of the stem, in addition to imparting stability distal to the PPFx while maintaining the proximal femoral bone.…”
Section: Introductionmentioning
confidence: 99%
“…[1][2][3][4] UCS B2 and B3 fractures have been traditionally managed with the use of modular long porous-coated tapered cementless stems with optional use of proximal bone allograft and cerclage cables. 3,[5][6][7][8] The construct popularity has been attributed to multiple factors, such as control in the adjustment of leg length, neck anteversion, and offset following implantation of the distal fixation portion of the stem, in addition to imparting stability distal to the PPFx while maintaining the proximal femoral bone. 3,[5][6][7][8] However, studies have also shown several disadvantages, such as higher rates of stem subsidence and intraoperative fracture, as well as implant failures including corrosion and junctional fractures at the proximal and distal segments of the prosthesis.…”
Section: Introductionmentioning
confidence: 99%